Virtual Inertial Control of Small- and Medium-Sized Wind Turbines on Mobile Offshore Platforms with DC Microgrids - Ruifang Zhang; Guoling Wang; Zhenyu Li; Fuqiao He; Chenghan Luo; Wensheng Cao (International Transactions on Electrical Energy Systems)
The renewable energy mobile offshore platform, which adopts the combined power supply of renewable energy and energy storage, is an important carrier for the development and utilization of marine resources. The randomness of renewable energy generation has a more prominent effect on the bus voltage stability and transient voltage deviation of the power system with small capacity and low inertia. Considering the operation and maintenance characteristics of the offshore platform, a virtual inertia control method for small- and medium-sized wind turbines is proposed. Firstly, by analyzing the characteristics of the renewable energy microgrid of the unattended offshore platform, considering the operating environment with high average wind speed at sea, the mechanical inertia in the wind turbine is selected as the energy source of virtual inertia. The structure of the wind power generation unit is analyzed, and small signal modeling is carried out. A virtual inertia control method based on power droop is proposed, and the rotational inertia and the damping coefficient are obtained from the characteristics of transient and steady-state analysis of the system. Finally, the DC microgrid experiment platform of the offshore platform is constructed, and it is verified that the proposed method makes full use of the characteristics of the offshore platform to enhance system inertia and improve the operational stability of the offshore platform DC microgrid system.